الدكتـور عبد الله الفياض ونتاجــه المعرفي في أدب الرحــــــــلات دراسة تاريخية - يوسف الركابي, عكاب (Journal of College of Education, 2020)
The study of the products of the Iraqi scientific, intellectual and cultural figures by researchers and academics has not received until recently a sufficient attention, but rather their attention has been focused on studying the personalities themselves and their roles in leading the society and the state without paying attention to their cognitive products, and in this research we will address some historical personal products that have broad contributions in the fields of knowledge Historical and literary, to shed light on an aspect of the products of the scholar and historian Dr. Abdullah Al-Fayyad in the field of travel literature, as we dealt in detail with everything related to the literature of trips that came in his published and unpublished works those works that circulated with Here are the countries of Iran, Turkey, Democratic Germany and some Iraqi cities